(untitled) (Bangladesh Journal of Agricultural Research, 2017)
Two wheel tractor (Power tiller) is the common means of soil tillage and other farm operations in Bangladesh due to easy access in fragmented land size with affordable price. A low cost and small robust 2WT driven (12 hp) No-till seeder has been developed with press wheel attachment and inclined plate seed meter assembly in Farm Machinery & Postharvest Process Engineering Division, BARI, Bangladesh for seeding different kinds of seeds. This is a pull type implement hitched at drawbar point of 2WT replacing the regular rotary part. The developed No-till seeder was used in the farmers field of Rajshahi areas for wheat, maize, pulses, and rice establishment during the year 2011-2014. The planter can pull 4 tynes in soft and medium hard soil but 3 tynes for hard soil. The planter was capable to apply seed and fertilizer in the furrows. The width and depth of the furrow opening were 30 mm and 60 mm, respectively. The planting depth, row spacing and seed rate can be adjusted according to standard practices. The No-till seeder works effectively through high density crop residue (1.5-2.4 t/ha) without any problem as there are sufficient residue clearances between toolbar and ground surface. Depending on the level of weed situation, round up herbicide was applied 2 days before of planting. There were significant yield difference in wheat, pulses but rice yield was lower than conventional transplanting method. No-till planted crops show less lodging tendency compare to conventional planted crops. There were significant cost differences between no-till and conventional method. The planting costs of wheat and maize in Notill system were 60% and 86% less than conventional planting method. It also reduces the average turn around time 7-9 days between the two crops. The effective area coverage by the seeder was 0.13ha/hr. The No-till seeder is a low cost (US 350-400; without power unit), light in weight and local manufacturer can fabricate complete unit within a short period of time. The No-till seeder can be used in other countries where 2WT is the common farming equipment. Bangladesh J. Agril. Res. 42(1): 27-34, March 2017